(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This article discusses the ongoing reforms in the field of education in our country, the support for youth with disabilities, and reflections on educational privileges provided to them. It highlights our views on the implementation of inclusive education for youth with disabilities, alongside the new edition of the Law on Education, which emphasizes inclusive education and equality for all in the educational process.